Pengaruh Workplace Favouritisme, Workplace Violence terhadap Turnover intention Dimediasi oleh Social Support Guru di Sekolah - Amalia Fitri Dwi Widyati (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
A school can be the best school when it has a teacher who is competent in their field, but a teacher can reduce school performance if he does not feel valued by the school so that a competent teacher makes turnover intention. Teachers make turnover intentions caused by many things, namely workplace favouritism, workplace violence and social support in the school environment. This study aims to determine the influence of workplace favouritism, workplace violence and social support on turnover intention. The subjects of this study were 45 teachers from elementary and junior high school units at XYZ schools in the Balaraja area. The research design used is path analysis with a quantitative approach. The results of the study found that workplace favouritism has a positive effect on turnover intention, workplace violence has a positive effect on turnover intention, social support has a positive effect on turnover intention, workplace favouritism through social support has a positive effect on turnover intention and workplace violence through social support has a positive effect on turnover intention.